Military parents' perceptions of separation for their younger children. Issue 12 (16th December 2021) - Agazio, Janice; Cunningham, Craig A.; Amos-Mejia, Danielle
ABSTRACT: Many studies are available in the literature considering effects of deployment on older school age and adolescent children, but less is known about the effects on younger children. The purpose of this study was to describe the experience of deployment/separation for military children aged 4–10 years from both the deployed parent and stay-at-home parent's experiences. Parents completed demographics followed by an interview to describe the child's reaction to separation. Thematic analysis was used to identify children's reactions and intervention strategies. Thirty-eight families, encompassing 57 children aged 4–10 who experienced a separation or deployment within the past 2 years participated. Interviews included 24 military members and 34 spouses (most frequently the mothers) completed the interview and research instruments. Interview data revealed a turbulent experience for families resulting from frequent and repeated separations. Parents actively employed strategies garnered from military-provided materials and informal interaction with other military parents. The different perspectives provided new insights as to the strategies military families find successful during separations and will be useful in providing anticipatory guidance.